The Influence of Bud Positions on the Changes in Carbohydrates and Nitrogen in Response to Hydrogen Cyanamide During Budbreak in Low-Chill Kiwifruit - Wanichaya Chaiwimol; Wisuwat Songnuan; Hitoshi Ohara; Yotin Juprasong; Aussanee Pichakum (Horticulturae)
Climate change has contributed to a decline in winter chilling accumulation, a critical requirement for budbreak in temperate fruit crops. Its consequence has been a reduction in fruit production. To compensate for insufficient chilling, hydrogen cyanamide (HC) is widely applied, though its effectiveness remains limited. This study investigated the effect of HC application on budbreak in low-chill kiwifruit under warm conditions by correlating phenological responses with changes in carbohydrate and nitrogen concentrations in bark tissues across bud positions. Phenological observations revealed the highest budbreak percentage and total flower buds at the apical position. HC significantly increased budbreak by 58.82% at the apical position and by 375% at the middle position, with corresponding increases in total flower buds by 148.78% and 1066.67%, respectively. Additionally, shoot lengths were uniform among bud positions in HC-treated canes, whereas non-treated canes showed shoot length heterogeneity. Moreover, HC treatment triggered an earlier and more pronounced reduction in soluble sugars (sucrose and hexoses) concentrations along the gradient from apical to basal bud positions, where the response was strongest at the apical position, which was strongly associated with enhanced budbreak percentages and total flower bud formation. While total nitrogen content was highest in the apical position, it was unaffected by HC application. These findings indicate that HC may promote budbreak by enhancing the mobilization and consumption of soluble sugars for bud growth, thereby improving budbreak performance, flower bud production, and uniform shoot development in low-chill kiwifruit under warm conditions.